(untitled) (Journal of Comparative & International Higher Education, 2024)
Fries-Britt et al.’s (2014) Learning Race in a U.S. Context (LRUSC) emergent framework holds significant prominence in international student literature as the pioneering framework to theorize the perceptions of race and responses to racialized experiences among college students of color born and raised outside of the U.S. This scholarly paper analyzes nine peer-reviewed articles published after 2014, utilizing micro-level narratives that delve into the racial learning experiences of diverse international students within the U.S. context. The aim is to assess the framework’s relevance and suggest potential updates a decade after its initial publication. The findings show that the framework is still generally applicable but can benefit from incorporating the following revisions: 1) broadening the scope of racial encounters; 2) emphasizing the impacts of the home country context; and 3) leaving the outcomes of racial learning open.